Perancangan Mebel Untuk Desain Interior Rumah Susun Dengan Material Cardboard (Studi Kasus: Rusun Wonorejo Surabaya) - David Pramudita Santoso; Mariana Wibowo (Intra, 2018)
Nowadays, people tend to have so much necessities, despite their low income. Therefore, the available area for furniture in living spaces are mostly incompatible to provide those needs, resulting in the large number of families living in flats. On the other hand, materials used for furniture sometimes could also become the obstacles. Thus, the alternative material offered by designer is cardboard, which usually used only as a wrapper and then being discarded. The idea creates a new research problem that is how to design multifunctional furniture for flats type of residential space using cardboard material. Therefore, the designer provides an alternative solution where multifunctional (modular) furniture designed from cardboards will be easily combined and arranged compactly. The explosing design method is used in the design process, in which analysis and programming toward the existing problems are keys to create an innovation. The result is 3 sets of furniture, each of which has 3 different types of furniture (desk-chair-storage cabinet). Moreover, each set of furniture can be arranged in a compact and modular way to accommodate the users’ needs.